Pengaruh Stimulasi Dan Fasilitasi Fisioterapi Terhadap Pertumbuhan Dan Perkembangan Motorik Bayi Usia 0-12 Bulan - Winingsih, Suwarni; Halimah, Nurul; Wardoyo, Puspo; Pradita, Angria (Jurnal Keperawatan Muhammadiyah, 2022)
Growth and development are two events that are different in nature but occur at the same time, are interrelated, and cannot be separated. Optimal motor growth and development is influenced by the stimulus obtained and the biological potential possessed, and both will interact with various interrelated factors, including genetic factors, biophysical-psychological-social factors and behavioral environmental factors. The study analyzes the growth and development of the motor before and after stimulation and physiotherapy.  The independent variables of the study are  stimulation and facilition physiotherapy, whereas the dependent  variables are the growth and development of 0-12 month-old babies. The number of respondents in this study are 21 people taken using lever-sampling techniques. The design of this research uses one group pretest and post test design.  The results of this study are p-value = 0.001 (p < 0.05), which suggests that stimulation and physiotherapy facilities affect the growth and development of the baby's motor in the 2021 physiotherapy baby spa Jember. There was a 0-12 - month delay in infant motor growth, in which 16 babies were stimulated and in physiotherapy were made (76.2%).  There has been an accelerated growth and development in infants aged 0-12 months after facilities and 14 infants with physiotherapy stimulation (66,7%). There is an increase in infant growth and development in which before and after stimulation and in physiotherapy can be made (16-2) 14 (66,7%) respondents, with an average increase of 7.5 and a total increase of 105. Thus, there is an impact of stimulation and physiotherapy on the growth and development of the baby's motor score of 0.001 < (α =0,05).